The kid with a bike [videorecording (DVD)] / = Le gamin au vélo - Dardenne, Jean-Pierre, 1951-; Dardenne, Luc, 1954-; France, Cécile de, 1975-; Doret, Thomas; Renier, Jérémie (Criterion collection, 2013)
Twelve-year-old Cyril, all coiled anger and furious motion, is living in a group home but refuses to believe he has been rejected by his single father. He spends his days frantically trying to reach the man, over the phone or on his beloved bicycle. It is only the patience and compassion of Samantha, the stranger who agrees to care for him, that offers the boy the chance to move on.